Effect of a Moderate-Intensity Aerobic Training on Joint Biomarkers and Functional Adaptations in Rats Subjected to Induced Knee Osteoarthritis - Martins, Jeanne Brenda; Mendonça, Vanessa Amaral; Aguiar, Grazielle Cordeiro; Fonseca, Sueli Ferreira da; Santos, Jousielle Márcia dos; Tossige-Gomes, Rosalina; Melo, Dirceu de Sousa; Oliveira, Murilo Xavier; Leite, Hércules Ribeiro; Camargos, Ana Cristina Resende; Ferreira, Anderson José; Coimbra, Cândido Celso; et al. (Frontiers in Physiology, 2019)
Background: Knee osteoarthritis (kOA) is a common chronic disease that induces changes in redox status and inflammatory biomarkers, cell death, and motor impairment. Aerobic training can be a non-pharmacological alternative to prevent the progression of the disease. Objective: To evaluate the effects of an 8 weeks moderate-intensity treadmill aerobic training program on redox status and inflammatory biomarkers and motor performance in kOA-like changes induced by monosodium iodoacetate (MIA) in rats. Methods: Twenty-seven rats were randomly divided into 3 groups: SHAM; induced kOA (OA); and induced kOA + aerobic training (OAE). Motor performance was evaluated by the number of falls on rotarod test, the total time of displacement and number of failures on a 100 cm footbridge. Data for cytokines and histology were investigated locally, whereas plasma was used for redox status biomarkers. Results: The OA group, compared to the SHAM group, increased 1.13 times the total time of displacement, 6.05 times the number of failures, 2.40 times the number of falls. There was also an increase in cytokine and in thiobarbituric acid reactive substances (TBARS) (IL1β: 5.55-fold, TNF: 2.84-fold, IL10: 1.27-fold, IL6: 1.50-fold, TBARS: 1.14-fold), and a reduction of 6.83% in the total antioxidant capacity (FRAP), and of 35% in the number of chondrocytes. The aerobic training improved the motor performance in all joint function tests matching to SHAM scores. Also, it reduced inflammatory biomarkers and TBARS level at values close to those of the SHAM group, with no change in FRAP level. The number of falls was explained by IL1β and TNF (58%), and the number of failures and the total time of displacement were also explained by TNF (29% and 21%, respectively). Conclusion: All findings indicate the efficacy of moderate-intensity aerobic training to regulate inflammatory biomarkers associated with improved motor performance in induced kOA-like changes, thus preventing the loss of chondrocytes.